Language Dynamism: A Cross-Cultural Analysis of Indonesian Political Leader Speech During Covid-19 Pandemic - Wulandari, Slara Ayu; Prihatin, Yoga; Santoso, Masfuad Edi (South Asian Journal of Social Sciences and Humanities, 2021)
Politicians achieve success thanks to the excellent use of rhetoric they use to convince audiences of the validity of their views, the use of elegant and persuasive language that is conveyed smoothly and carefully (Jones and Peccei (2004) as cited in Bayram (2010)). This research aims to find out how the speech strategy and communication style used by President Joko Widodo in his speech. And how it was when looking from cross-cultural perspective. The research started by Categorizing each phrase, sentence and sentences. Then analyzing the speaking strategy and style of communication used by President Joko Widodo by paying attention to every phrase, sentence, and sentences. Last, explaining from cross-cultural perspective. The result of this research shows that President Joko Widodo dominantly used argumentative strategy in both speeches. And for communication style analysis, it is found that President Jokowi used four different styles.